Global, regional, and national burden of tuberculosis and attributable risk factors for 204 countries and territories, 1990-2021: a systematic analysis for the Global Burden of Diseases 2021 study - Huafei Yang; Xinyi Ruan; Wanyue Li; Jun Xiong; Yuxin Zheng (BMC, 2024)
Abstract Background Tuberculosis (TB) remains a major global health threat. Despite ongoing efforts to control and eradicate TB, various factors including socioeconomic issues, policy modifications, and unexpected public health crises like COVID-19 pandemic have posed new obstacles to achieving TB elimination. This study aims to analyze the changes in global tuberculosis burden over the past 32 years, and provide scientific support for global initiatives targeting the eradication of TB in the post-pandemic period. Methods The data for this study were obtained from the Global Burden of Disease (GBD) 2021 database, with age-standardized incidence rate (ASIR), prevalence rate (ASPR), mortality rate (ASDR), and disability-adjusted life years (DALYs) as the primary assessment indicators. Dynamic changes in the TB burden were analyzed by estimating the annual percentage changes (EAPCs). The attributable ratios of six main risk factors to TB burden were calculated, and the correlation between the Socio-Demographic Index (SDI) and the TB burden was analyzed using Pearson correlation tests. Results The global TB incidence decreased from 8.6 million cases in 1990 to 8.4 million cases in 2021, with a corresponding decline in deaths. However, the TB burden remains higher among men than women. The highest incidence and mortality rates were observed in the age group of 15-69 years, with a notable gender disparity, especially in Eastern Europe. These rates were generally elevated in low-income and lower-middle-income regions, with significantly higher Age-Standardized Incidence Rates and Age-Standardized Death Rates in males compared to females. A significant negative correlation was found between SDI values and TB burden. Analyzing risk factors from the Global Burden of Disease study, it was determined that globally, dietary risks, high body-mass index, high fasting plasma glucose, low physical activity, tobacco, and alcohol use were the main contributors to TB age-standardized Disability-Adjusted Life Years, with tobacco and alcohol use having the most significant impact. Analysis of risk factors suggests that tailored public health interventions for specific genders and regions can effectively lessen the TB burden.